Biocompatible, photo-responsive layer-by-layer polymer nanocapsules with an oil core: in vitro and in vivo study. Issue 187 (23rd February 2022) - Di Cicco, Chiara; Vecchione, Raffaele; Quagliariello, Vincenzo; Busato, Alice; Tufano, Immacolata; Bedini, Emiliano; Gerosa, Marco; Sbarbati, Andrea; Boschi, Federico; Marzola, Pasquina; Maurea, Nicola; Netti, Paolo A.
Abstract : In cancer therapy, stimulus-responsive drug delivery systems are of particular interest for reducing side effects in healthy tissues and improving drug selectivity in the tumoral ones. Here, a strategy for the preparation of a photo-responsive cross-linked trilayer deposited onto an oil-in-water nanoemulsion via a layer-by-layer technique is reported. The system is made of completely biocompatible materials such as soybean oil, egg lecithin and glycol chitosan, with heparin as the polymeric shell. The oil core is pre-loaded with curcumin as a model lipophilic active molecule with anti-tumoral properties. The trilayer cross-linkage is performed via a photoinitiator-free thiol-ene 'click' reaction. In particular, the system is implemented with an o -nitrobenzyl group functionalized with a thiol moiety which can perform both the thiol-ene 'click' reaction and the cleavage meant for controlled drug release at two different wavelengths, respectively. So the preparation and characterization of a photo-responsive natural nanocarrier (PNC) that is stable under physiological conditions owing to the thiol-ene cross-linkage are reported. PNC performance has been assessed in vitro on melanoma cells as well as in vivo on xenograft tumour-induced mice.